Використання автентичних матеріалів у процесі викладання англійської мови студентам-філологам - Рейда, О. А.; Івлєва, К. С.; Гулієва, Діна Олександрівна (Дрогобицький державний педагогічний університет ім. Івана Франка, 2019)
У статті зроблена спроба розглянути питання використання автентичних матеріалів у процесі навчання англійській мові студентів філологів, дано визначення поняттю "автентичні матеріали" та "навчально-автентичні матеріали". В рамках статті представлені головні аспекти використання автентичних матеріалів та пропонуються етапи роботи з автентичними матеріалами (підготовчий етап, етап безпосередньої роботи з матеріалом (текстовий), етап обговорення та творчий етап), запропоновані вправи до кожного етапу та визначені умови результативного використання автентичних матеріалів на занятті. Використання автентичних матеріалів у процесі підготовки студентів-філологів розглядається як засіб розвитку всіх компонентів іншомовної комунікативної компетенції: мовного, мовленнєвого, соціокультурного, компенсаторного, академічного компоненту.

The article aims to consider the authentic materials using in the process of English language teaching to students philologists, the concept of “authentic materials” and concept of “training and authentic materials” has been defined. It has been emphasized that text material can also be used in class according to modern methods of teaching English, which is specially developed or processed by methodologists in order to adapt it to the specific needs of students: the definitions of these texts has been presented: (semi-authentic texts, edited authentic texts, approximately-turned authentic texts, near-authentic texts, authentic-looking texts, learner authentic texts). The main aspects of authentic materials using and working phases with authentic materials (preparatory stage, the stage of direct work with training material (text), the discussion stage and creative stage) have been presented in this article, the exercises for each stage are proposed and the requirements for the successful use of authentic materials in the classroom have been listed. The authentic materials using of students philologists training are considered as a means of all components development of foreign language communicative competence: language, speech, social and cultural, compensatory and training components; forms of lexico-grammatical, intonational, speech, emotional example, restores the usual conditions of real communication, reflecting both the real situations and imaginary ones. The authentic materials linking the elements of the lesson can organize and regularize the training stages. In addition, they are a synthesis of visual, acoustic, motor, speech, situational, detail and figurative demonstrativeness. The article analyzes the specifics of the authentic materials selecting for the purposes of its using in English classes in the training process, the requirements have been listed: authenticity, functionality (different themes and genres of authentic materials, their meaningful significance), didactic and cognitive value of the authentic resources. The article mentioned the active practice of authentic materials using in teaching English to students is limited by the level of students’ language knowledge and certain difficulties concerning socio-cultural aspect.
Authentic materials using in the process of english language teaching to students philologists
Keywords: іншомовна комунікативна компетенція; міжкультурна комунікація; когнітивні вміння; навчальний процес; філологія; foreign-language communicative competence; student philologist; authentic material; educational material; intercultural communication; cognitive competence